Effect of organic and inorganic nitrogen fertilizers on quality of barley (Hordeum vulgare L.) - Chavarekar, S.; Thakral, S. K.; Meena, R. K. (Annals of Agricultural Research, 2014)
A field experiment was conducted during the winter season (rabi) of 2010-11 at Hisar to determine the effect of organic and inorganic nitrogen fertilizers on quality of barley. Nitrogen application significantly influenced the protein, bold and thin per centage, malt friability and nitrogen uptake by grain and straw. The treatment 100% recommended dose of nitrogen (RDN) through chemical fertilizers + Azotobacter recorded significantly higher protein per centage (10.8%). The malt extract affected inversely with the increase in nitrogen content and protein per centage of grain. The highest malt content recorded with control (90.1%). The agronomic nitrogen use efficiency was recorded highest with 100% RDN through chemical fertilizers + Azotobacter (25.98 kg grain/kg N applied)